Role of oxidative stress in cataractogenesis - Bhatia, Geeta; Sontakke, A. N.; Abhang, Subodhini (International Journal of Research in Medical Sciences, 2017)
Background: Cataract is a multifactorial disease and is a major cause of blindness in india. Oxidative stress is thought to be a major factor to initiate the process of cataractogenesis. It is today well established fact that oxidative stress participates in both age-related (senile) and diabetes-induced cataract (diabetic). Oxidative damage to the lens most likely arises as a consequence of an impaired antioxidant defence system, due to increased generation of ROS both by age and diabetes. The present study was designed to determine role of oxidative stress in cataractogensis and to compare levels of oxidative stress markers in senile and diabetic cataract patients. Methods: Serum malondialdehyde (MDA) and serum protein carbonyl (PC) were measured as indicator of oxidative stress whereas antioxidant status was assessed by estimating serum Total antioxidant capacity (TAC) and dietary antioxidants levels i.e vitamin C and vitamin E in senile and diabetic cataract patients compared with healthy controls. Results: The result reveal that the serum MDA and PC levels were significantly increased in patients with senile and diabetic cataract whereas serum TAC, vitamin C and Vitamin E were significantly reduced in senile and diabetic patients when compared with normal healthy controls. Conclusions: From the result, it is concluded that oxidative stress is in the foreground of cataract formation which includes senile and diabetic cataract. Oxidative stress produced in diabetic cataract patients is more as compared to senile cataract patients.